Risk factors and Perinatal Outcome of Umbilical Cord Prolapse in Sagamu, Nigeria - Lamina MA; Adefuye PO; Akinsanya FA; Odubena O (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2016)
Background: Umbilical cord prolapse is an obstetric emergency that threatens the life and well-being of the fetus and also increases maternal morbidity. Fetal survival in umbilical cord prolapse can be enhanced by prevention where risk factors are identified and prompt diagnosis and decisive intervention. Objective: The aim of this study was to determine the incidence, identify the risk factors associated with umbilical cord prolapse and document the perinatal outcome of cases of cord prolapse. Methods: This was a 13-year retrospective case-control study of cases of umbilical cord prolapse seen at the OOUTH, Sagamu, Southwestern Nigeria between January 1, 2000 and December 31, 2012. Result: During the study period, the incidence of umbilical cord prolapse was 1 in 122 deliveries (0.82%). The umbilical cord prolapse occurred in association with breech presentation five times (33.3%) and transverse lie eleven times (18.5%). The occurrence of breech presentation among the control cases was 8.6% (p<0.001) and that of transverse lie was 1.9% (p<0.001). There were also significant statistical differences between the cases of cord prolapse and controls in terms of prematurity, low birth weight, unbooked status and multiparity. The perinatal rate was 222/1000 (22.2%) compared to the perinatal mortality of 68/1000 (6.8%) for the control group. Conclusion: It is suggested that pregnant women should be encouraged to register early in pregnancy for antenatal care as this will enhance early identification of the risk factors and appropriate management instituted to reduce perinatal mortality.